Performance, motivation, and enjoyment in young female basketball players: An interdisciplinary approach - Soares, A. L. A.; Leonardi, T. J.; Silva, J.; Nascimento, J. V.; Paes, R. R.; Gonçalves, C. E.; Carvalho, H. M. (Journal of Sports Sciences, 2020)
The purpose of this study was to examine the variation in accumulated basketball training experience, body size, functional performance, deliberate practice motivation, achievement and competitiveness motivation and sources of enjoyment among young female basketball players, partitioning the potential variation by individuals´ biological characteristics (menarche status) and contextual characteristics (competitive age group and competitive level). We considered 114 adolescent female basketball players aged 14.3 (1.8) years. We used multilevel regression and poststratification estimations. The adolescent female basketball players selected for state-level had more accumulated experience, were taller and with better functional performance. Conditional on the data, youth female coaches tend to value (probably overvalue) size and function when selecting/promoting players, even at early age groups, likely contributing to an overrepresentation of early maturing girls in at early age groups. Players from club- and state-level were similarly highly motivated for deliberate practice and to achievement. Only for competitiveness, state-level players had higher values than club level players. The sources of enjoyment were influenced by context (competitive levels) for self-referenced competencies and others-referenced competencies. Structured programs of training and competition in youth female basketball provide a nurturing environment for the development of players´ engagement and commitment to training and excellence attainment.